2000
DOI: 10.1016/s0006-3495(00)76857-3
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Denaturing of Bacteriorhodopsin by X-Ray Scattering from Oriented Purple Membranes

Abstract: We present a temperature-dependent x-ray diffraction study of thin films of purple membranes (PMs) with the native membrane protein bacteriorhodopsin (BR). The high degree of alignment with respect to the silicon substrates allows for the application of modern interface-sensitive scattering techniques. Here we focus on the structural changes of BR in PMs at the thermal denaturing transition. A partial unfolding of the helices is observed rather than the complete unfolding process known from helix to coil trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…To address this point, we determined the free activation energy from unfolding rates measured at different temperatures in the physiological range. [66] In line with spectroscopic and calorimetric studies that reported no significant structural or heat capacity changes of bacteriorhodopsin [71][72][73] no clear temperature dependence of the activation energies could be identified by SMFS experiments. [66] Therefore the temperature-induced increase in unfolding rates observed by SMFS may be attributed to the kinetics of a thermally driven unfolding process.…”
mentioning
confidence: 69%
“…To address this point, we determined the free activation energy from unfolding rates measured at different temperatures in the physiological range. [66] In line with spectroscopic and calorimetric studies that reported no significant structural or heat capacity changes of bacteriorhodopsin [71][72][73] no clear temperature dependence of the activation energies could be identified by SMFS experiments. [66] Therefore the temperature-induced increase in unfolding rates observed by SMFS may be attributed to the kinetics of a thermally driven unfolding process.…”
mentioning
confidence: 69%
“…Alterations of the protein's helical structure upon thermal denaturation have been suggested based on infrared spectroscopy and HDX measurements. 82,83 Dynamic light scattering indicates partial disruption of the purple membrane patches. 83 Labeling of heated BR leads to significant oxidation of M20 (helix A) and M118 (helix D) with F u corr ≈ 0.8, whereas M56, M60, M145, and M209 remain fully protected (Fig.…”
Section: Structural Interpretation-br After Heat Exposurementioning
confidence: 99%
“…10 X-ray diffraction experiments also indicate that there is a gel-to-liquid transition of the lattice during the premelting transition showing the local order of the trimers is maintained, but the trimeric unit cells are no longer packed in the hexagonal lattice. 12 Therefore, it may suggest that the appearance of "nonisland" structure corresponds to the premelting transition. Also, it might be expected that the "nonisland" structure would convert back to 2D crystal structure if pH is decreased from 12.3 to below 12.0 as the premelting transition is reversible.…”
Section: Discussionmentioning
confidence: 99%
“…9 The thermal denaturation of bR has also been extensively studied by differential scanning calorimetry (DSC), ultraviolet-visible absorption spectroscopy, CD spectroscopy, and Fourier transform infrared (FTIR) absorption spectroscopy, 7,10,11 as well as X-ray scattering. 12 The main results summarized that bR undergoes a reversible premelting structural transition at 78-80°C and an irreversible melting transition at about 96°C, depending on the pH and metal ion concentration. 10,11 However, until now there is no report about the direct observation of PM during denaturation which is supposed to give the firsthand information about the structural changes.…”
Section: Introductionmentioning
confidence: 98%